Elimination of micropollutants by activated carbon produced from fibers taken from wastewater screenings using hydrothermal carbonization. (1st April 2018) - Benstoem, F.; Becker, G.; Firk, J.; Kaless, M.; Wuest, D.; Pinnekamp, J.; Kruse, A.
Abstract: Activated Carbon (AC) can be used to reduce organic micropollutants (OMPs) in wastewater treatment plants (WWTPs). While producing ACs conventionally still damages the environment, this can be reduced by using renewable raw material from waste streams und producing AC locally. In this study, fibers (toilet paper) were separated out of wastewater by screening WWTP influents in full scale and then used as a no-cost, carbon-rich and heavy metal-poor raw material to produce ACs. Pretreatment was hydrothermal carbonization (HTC). Thereafter, they were activated using KOH to generate activated carbons (HTC-ACs). Their functional groups were characterized using FT-IR, and the alteration of their chemical composition was traced by elementary analysis. Adsorption tests were performed with nitrogen (BET surface) and methylene blue as standard tests. The adsorption capacity was tested with WWTP effluent and the removal of UVA254 as a surrogate for OMP removal was measured. After HTC and activation 13–16% of the fibers dry mass was obtained as HTC-ACs. Higher dehydration and formation of aromatic structures on the HTC-ACs were detected with FT-IR as HTC and activation temperature increased. BET surface and methylene blue adsorption of some HTC-ACs was higher than the Reference AC. Nevertheless, their ability to reduce OMPs is still lower than the Reference AC due to the different nature of their functional groups and their microporous structure that is not fully accessible for OMPs in real wastewater. Further research has to be carried out to adjust the production process so as to obtain mesoporous HTC-ACs tailored to reduce OMP concentrations and to close the carbon loop within WWTPs. Graphical abstract: Image 1 Highlights: Activated carbons (ACs) were produced from fibers screened from municipal wastewater using hydrothermal carbonization. Some show larger BET areas and methylene blue adsorption than commercial AC. Their removal of micropollutants from wastewater is lower than commercial AC. All ACs needed for wastewater treatment could be derived from screened fibers.